Reinvigorating food production in Nepal: Strengthening the irrigation–agriculture nexus - Adhikari, Manju; Shrestha, Nirman; Mishra, Krishna Kumar; Singh, Sunil Kumar; Nepal, Santosh (CGIAR System Organization, 2023)
Nepal is increasingly dependent on food imports, which rose by about 60% between 2015 and 2020, according to foreign trade statistics. This trend threatens Nepal’s agricultural future and undermines food security – an undesirable outcome for a country already classified as having a ‘moderate level of hunger’ in the 2022 Global Hunger Index.